(untitled) (Journal of Universal Science Research, 2025)
The article shows the role of compaction in time and space in increasing the productivity of irrigated crop rotations and saturating agricultural crops with two- and three-component mixed components. Particular attention is paid to increasing the efficiency of irrigation water use by forage crops. Particular attention is paid to increasing the efficiency of using forage crops through irrigation, taking into account agrotechnical requirements.